Genes found in partial sequencing of Phytophthora cinnamomi - Santos, Luís (2016)
Members of the oomycete cause extensive losses in agriculture and widespread degradation in natural plant communities, being responsible for the death of thousands of trees every year. Two of the representative species are Phytophthora infestans, which causes late blight of potato, and Phytophthora cinnamomi, which causes chestnut ink disease, responsible for losses on sweet chestnut production in Europe. Genome sequencing efforts have been focused on the study of three species: P. infestans, P. sojae and P. ramorum. Phytophthora infestans has been developed as the model specie for the genus, possessing excellent genetic and genomics resources including genetic maps, BAC libraries, and EST sequences. Our research team is trying to sequence the genome of P. cinnamomi in order to gain a better understanding of this oomycete, to study changes in plant-pathogen relationships including those resulting from climate change and trying to decrease the pathogen’s impact on crops and plants in natural ecosystems worldwide. We present here a preliminary report of partially sequenced genomic DNA from P. cinnamomi encoding putative protein-coding sequences and tRNAs. Database analysis reveals the presence of genes conserved in oomycetes.